Influence of Attention-Deficit Hyperactivity Disorder (ADHD) on Academic Achievement of Learners in International Primary Schools in Mombasa (Kenya) and Kampala (Uganda): A Comparative Study - Biirah, Judith; Anika, Alice; Zigler, Richard Simon (European Scientific Journal, ESJ, 2018)
Attention deficit hyperactivity disorder (ADHD) is one of the most prevalent disorders among school-going children. The aim of this study was to compare academic achievement of learners with and without ADHD in international primary schools of Mombasa (Kenya) and Kampala (Uganda). A comparative study was conducted among 377 respondents using Attention Deficit Hyperactivity Disorder Scale Questionnaire (SNAP-IV) which assessed the three ADHD subtypes in form of a closed-ended questionnaire. Results revealed that learners with ADHD had low overall academic achievement compared to those without ADHD in Mombasa (p <.001) and Kampala, (p <.001). Boys with ADHD in Mombasa had better grades than girls (M = 168.51, SD = 32.50 vs. M = 160.00, SD = 39.07) while girls with ADHD in Kampala had better grades than boys (M = 103.50, SD = 24.77 vs. M = 93.45, SD = 24.71). Learners with ADHD Inattentive subtype were greatly impaired compared to those with ADHD Hyperactive-Impulsive and Combined subtypes in both cities. ADHD significantly predicted academic achievement with higher variability in Kampala (55%) than Mombasa (10%). Attention-deficit hyperactivity disorder has a negative impact on academic achievement of learners with the condition. The study recommended integration of ADHD screening in school health services to enable early detection and management of the condition.